ANALISIS HUKUM PEMUTUSAN LISTRIK AKIBAT TUNGGAKAN REKENING LISTRIK YANG DILAKUKAN OLEH KONSUMEN (STUDI KASUS PT. PLN (PERSERO) UP3 PAREPARE) - Ibrahim Fattah, Muthmainnah, Citra Maulani (FAKULTAS HUKUM UM PAREPARE, 2023)
This Study Aims to Determine the Legal Analysis of Electricity Disconnection Due to Arrears in Electricity Bills Made by Consumers and the Obstacles Faced by PT PLN (Persero) UP3 Parepare in Disconnection Electricity Due to Arrears in Electricity Bills Made by Consumers. This uses research qualitative descriptive research with an empirical approach normative. Data obtained from Literature Observational Studies Interview results Library Research Methods and documentation. The results of the study show that the legal analysis of electricity disconnection due to arrears in electricity bills carried out by consumers in the city of Parepare can be seen from the large number of people who do not comply with the rules of the power purchase agreement (SPJBTL) where consumers often make arrears in paying electricity bills. Then the constraints in the procedure for disconnection electricity to consumers carried out by the tusbung officer (Disconnection and Connection) PT. PLN (Persero) UP3 Parepare towards consumers in the use of electric current, such as limited human resurces or tusbung officers so that performance becomes less than optimal and communication between consumers is not good.